Polio vaccination coverage among children aged 12-23 months in a health block in North Kerala - Lakshmanan, Manju Thandayan; Karunakaran, Usha (International Journal Of Community Medicine And Public Health, 2020)
Background: Polio (poliomyelitis) is a highly infectious viral disease which affects the nervous system and can result in irreversible paralysis within hours. There is no cure for polio, hence it becomes necessary to prevent the disease through vaccination. Thus, the objective of this study was to evaluate the polio vaccination coverage among children aged 12-23 months in a health block in Kannur, North Kerala. Methods: A community based cross sectional study was conducted among the children in the age group of 12-23 months residing in Pappinisseri block of Kannur district. Stratified random sampling was used. The details of 321 children were obtained using a pre-tested semi-structured questionnaire. The data was entered into Microsoft Excel 2007 spread sheet and analyzed using SPSS version 16.0 software. Results: Of the 321 children, males constituted 173 (54%) and females constituting 148 (46%). The total coverage of oral polio vaccines (OPV) (considering OPV-0, 1st, 2nd and 3rd doses) was found to be 92.8% and the inactivated poliomyelitis vaccine (IPV) coverage (IPV 1st and 2nd doses) to be 90.7%. Also, majority of the respondents were unaware of the use of OPV and IPV vaccines in the UIP. Conclusions: In spite of the efforts taken by the Government and the health officials, the OPV and IPV coverage has not reached 100% and also, the knowledge of mothers regarding the diseases prevented by the vaccines were very low. The reasons for this needs to be further evaluated.